Subcutaneous fluid administration in elderly subjects: validation of an under-used technique - Lipschitz, S; Campbell, A J; Roberts, M S; Wanwimolruk, S; McQueen, E G; McQueen, M; Firth, L A (Journal of the American Geriatrics Society (JAGS), 1991)
In a crossover study in six volunteers over the age of 65, absorption of 500 mL of normal saline given subcutaneously was compared with that given intravenously. Tritiated water and technetium pertechnetate were used as water tracers. Tritium radioisotope levels in the blood increased in a smooth curve during subcutaneous infusion, reaching equilibrium levels within 60 minutes. The area under the curve after subcutaneous infusion was almost identical to that after intravenous infusion in all subjects. Radioactivity could not be demonstrated at the subcutaneous site 1 hour after completion of the infusion. Subcutaneous infusion is an effective method of giving fluid to elderly people and deserves more widespread use.